OP0216 Efficacy and safety of tofacitinib, an oral janus kinase inhibitor, or adalimumab in patients with active psoriatic arthritis and an inadequate response to conventional synthetic disease-modifying antirheumatic drugs (CSDMARDS): a randomised, placebo-controlled, phase 3 trial. (15th June 2017) - Mease, PJ; Hall, S; FitzGerald, O; Heijde, D van der; Merola, JF; Avila-Zapata, F; Cieślak, D; Graham, D; Wang, C; Menon, S; Hendrikx, T; Kanik, KS
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for treatment of psoriatic arthritis (PsA). Objectives: To assess the efficacy and safety of tofacitinib vs placebo (PBO) in patients (pts) with active PsA. Methods: Eligible pts in this randomised, PBO- and active-controlled, 12-month Phase 3 trial had ≥6-months' PsA diagnosis, fulfilled CASPAR criteria, had active arthritis (≥3 tender/painful and ≥3 swollen joints) and active plaque psoriasis at screening, inadequate response to ≥1 csDMARD, and were tumour necrosis factor-inhibitor (TNFi)-naïve. 422 pts were randomised 2:2:2:1:1 to tofacitinib 5 or 10 mg twice daily (BID), adalimumab 40 mg subcutaneous injection every 2 weeks, or PBO (advancing to tofacitinib 5 or 10 mg BID at Month [M]3). Stable treatment with 1 csDMARD was required. Primary endpoints comparing tofacitinib vs PBO were ACR20 response rate and change from baseline in Health Assessment Questionnaire Disability Index (ΔHAQ-DI) at M3. Secondary endpoints included: ACR20 response rates and ΔHAQ-DI through M12; pts achieving ACR50, ACR70, ≥75% improvement of PASI and PsARC at all time points; and changes from baseline in LEI, Dactylitis Severity Score and SPARCC Enthesitis Index. Radiographic progression was assessed by van der Heijde-modified Total Sharp Score (mTSS). Results: 96.9% of pts were white and 53.3% were female; mean age was 47.9 years. 96.2% and 88.4% of pts completed M3 and M12, respectively. At M3, tofacitinib 5 and 10 mg BID significantly improved ACR20 response rates (50.5% [p≤0.05] and 60.6% [p<0.0001] vs 33.3%; Fig 1 A) and ΔHAQ-DI (-0.35 [p≤0.05] and -0.40 [p<0.001] vs -0.18; Fig 1 B) vs PBO, with responses maintained to M12 (Fig 1 C&D). Greater efficacy was also seen for adalimumab vs PBO. Tofacitinib 5 and 10 mg BID were superior to PBO for ACR20 response rates at Week 2 (22.4% [p<0.001] and 31.7% [p<0.0001] vs 5.7%; Fig 1 C). Secondary endpoints supported primary findings (data not shown). >91% of pts were radiographic non-progressors at M12 (defined as an increase from baseline in mTSS ≤0.5). M12 safety findings were similar between groups (Fig 1 E). The most common adverse events were upper respiratory tract infection (7.5–10.6%), nasopharyngitis (7.5–11.5%) and headache (3.8–10.6%). Conclusions: In TNFi-naïve pts with active PsA, tofacitinib was superior to PBO in ACR20 response rates and ΔHAQ-DI at M3, with superiority vs PBO as early as Week 2 for ACR20, which was maintained to M12. No new safety risks were identified vs previous studies in other indications. Acknowledgements: Previously presented at ACR 2016, to be presented at AAD 2017 and reproduced with permissions. This study was sponsored by Pfizer Inc. Editorial support was provided by AG McCluskey of CMC and was funded by Pfizer Inc. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, CORRONA, Dermira, Janssen, Eli Lilly, Merck, Novartis, Pfizer Inc, Sun, UCB, Zynerba, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Novartis, Pfizer Inc, UCB, S. Hall Consultant for: AbbVie, Celgene, Eli Lilly, Janssen, Pfizer Inc, Roche, O. FitzGerald Grant/research support from: AbbVie, Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, Speakers bureau: Celgene, Janssen, Novartis, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli Lilly, Galapagos, Janssen, Merck, Novartis, Pfizer Inc, Roche, Sanofi-Aventis, UCB, Employee of: Imaging Rheumatology BV, J. Merola Grant/research support from: Biogen Idec, Consultant for: AbbVie, Amgen, Biogen Idec, Eli Lilly, Janssen, Momenta, Mallinckrodt, Novartis, Pfizer Inc, Speakers bureau: AbbVie, Eli Lilly, F. Avila-Zapata: None declared, D. Cieślak: None declared, D. Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc